Can the Liebowitz Social Anxiety Scale - self-report version be used to differentiate clinical and non-clinical SAD groups among Brazilians? - Larissa F Santos; Sonia R Loureiro; José A S Crippa; Flávia L Osório (PLoS ONE, 2015)
The Liebowitz Social Anxiety Scale (LSAS) was the first evaluation instrument developed for screening for the signs and symptoms of Social Anxiety Disorder (SAD) and is currently still the most used worldwide. The aim of this study is to evaluate the ability of the LSAS - self-report version (LSAS-SR) to discriminate different Social Anxiety Disorder (SAD) clinical groups.The sample was composed of Brazilians university students, allocated into three different groups, i.e., cases (C=118), non-cases (NC=95) and subclinical cases (SC=39). To achieve the aim, calculations of the ROC Curve and ANOVA were performed.The results found were excellent regardless of the technique used, highlighting the discriminatory capacity of the LSAS-SR. The score equal to or greater than 32 is suggested as a cutoff score for the Brazilian population, since this presented balance between the standards evaluated and the ability to differentiate both clinical and subclinical SAD cases from non-cases.Despite the specific sample used in this study being composed only of university students, the use of the LSAS-SR can be indicated, in the Brazilian setting, for SAD screening in both clinical and research contexts.